Thymine Sensitizes Gram-Negative Pathogens to Antibiotic Killing - Liu, Yuan; Yang, Kangni; Jia, Yuqian; Shi, Jingru; Tong, Ziwen; Wang, Zhiqiang (Frontiers in Microbiology, 2021)
Diminished antibiotic susceptibility of bacterial pathogens is an increasingly serious threat to human and animal health. Alternative strategies are required to combat antibiotic refractory bacteria. Bacterial metabolic state has been shown to play a critical role in its susceptibility to antibiotic killing. However, the adjuvant potential of nucleotides in combination with antibiotics to kill Gram-negative pathogens remains unknown. Herein, we found that thymine potentiates ciprofloxacin killing against both sensitive and resistant E. coli in a growth phase-independent manner. Similar promotion effects are also observed for other bactericidal antibiotics including ampicillin and kanamycin in the fight against four notorious Gram-negative bacteria (E. coli, S. enteritidis, A. baumannii and P. aeruginosa). The mechanisms underlying this finding is that exogenous thymine could upregulate bacterial metabolism including increased TCA cycle and respiration, which thereby promote the production of ATP and ROS. Subsequently, metabolically inactive bacteria were converted to active bacteria and restore its susceptibility to antibiotic killing. In Galleria mellonella infection model, thymine effectively improved ciprofloxacin activity against Gram-negative bacteria. Taken together, our results demonstrated that thymine potentiates bactericidal antibiotics activity against Gram-negative pathogens through activating bacterial metabolism, providing a universal strategy to overcome Gram-negative pathogens.